2020
DOI: 10.1142/s0219720020500122
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of Alzheimer’s brain sequencing data reveals absence of purported HHV6A and HHV7

Abstract: Readhead et al. recently reported in Neuron the detection and association of human herpesviruses 6A (HHV6A) and 7 (HHV7) with Alzheimer’s disease by shotgun sequencing. I was skeptical of the specificity of their modified Viromescan bioinformatics method and subsequent analysis for numerous reasons. Using their supplementary data, the prevalence of variola virus, the etiological agent of the eradicated disease smallpox, can be calculated at 97.5% of their Mount Sinai Brain Bank dataset. Reanalysis of Readhead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Examination of brains from AD patients failed to find HHV-6A/B DNA more often than in controls (301). Reexamination of the same data sets examined in reference 243 did not support the original conclusions about the presence of HHV-6A/B in AD brains (301,303,304). The amount of HHV-6A/B nucleic acid in diseased tissue or blood, and/or antibody levels, correlates with the severity of the disease.…”
Section: Conclusion: Hhv-6a/b and Admentioning
confidence: 92%
See 1 more Smart Citation
“…Examination of brains from AD patients failed to find HHV-6A/B DNA more often than in controls (301). Reexamination of the same data sets examined in reference 243 did not support the original conclusions about the presence of HHV-6A/B in AD brains (301,303,304). The amount of HHV-6A/B nucleic acid in diseased tissue or blood, and/or antibody levels, correlates with the severity of the disease.…”
Section: Conclusion: Hhv-6a/b and Admentioning
confidence: 92%
“…Finally, Chorlton found numerous problems in the original analysis and demonstrated that the virus detection algorithm used by Readhead et al "likely vastly overestimates viral read counts" and "probably identifies viral reads when none are present" (304). Readhead et al challenged this conclusion (305).…”
Section: Evidence Linking Vzv With Admentioning
confidence: 99%
“…Chorlton [44], on analysing the supplementary data of Readhead et al with Krak-enUniq, a method which he described as a fast yet highly sensitive method, detected no HHV7, and detected HHV6A in 13% of the samples that had been reported with the highest HHV6A abundance; 13%, as he stated, was consistent with previous research and he commented that almost all previous reports have relied on nucleic acid amplification for detection of HHV6A and HHV7, which is far more sensitive than shotgun sequencing. Further, based on Supplementary Table S2 from Readhead et al, he calculated viral prevalence based on their modified Viromescan, and found that in the main Mount Sinai Brain Bank (MSBB) dataset, HHV6A and HHV7 were detectable in 27% and 30% of 602 brain samples, respectively.…”
Section: Possible Involvement Of Hhv6 In Admentioning
confidence: 99%
“…Recent findings have confirmed a causative role of viruses of the Herpes family in AD [ 45 ] and a relevant relationship of Human Herpes virus 6 (HHV-6) and 7 (HHV-7) with the disease. However, discordant data regarding a pathogenetic link of HHV-6 and HHV-7 with AD are also on record [ 46 , 47 ]. Therefore, the association of these viruses with the disease deserves further investigation.…”
Section: Alzheimer Disease Chronic Inflammation the Amyloid-β And Virus Infectionmentioning
confidence: 99%